Wood Ash from Bread Bakery as Partial Replacement for Cement in Concrete - Raheem, Akeem Ayinde; Adenuga, Olumide A (International Journal of Sustainable Construction Engineering and Technology, 2013)
This paper reports the results of experiments evaluating the use of wood ash from bread bakery as partial replacement for ordinary Portland cement in concrete. The chemical composition of the wood ash as well as the workability and compressive strength of the concrete were determined. Wood ash was used to replace 5% - 25% by weight of the cement in concrete. Concrete with no wood ash serves as the control. The mix ratio used was 1:2:4 with water to binder ratio maintained at 0.5. The Compressive strength was determined at curing ages 3, 7, 28, 56, 90 and 120 days. The results showed that wood ash from bread bakery is a Class F fly ash since the sum of (SiO2 +Al2O3 +Fe2O3) is greater than 70%. The compressive strength of wood ash concrete increases with curing period and decreases with increasing wood ash content. There was a sharp decrease in compressive strength beyond 10% wood ash substitution. It was concluded that a maximum of 10% wood ash substitution is adequate for use in structural concrete